Analisis Kerusakan Permukaan Jalan Berdasarkan Penilaian Dengan Metode SDI Dan IRI - Maulana, Miftah; Rulhendri; Chayati, Nurul (Indonesian Society of Applied Science, 2023)
Transportation infrastructure in the form of roads holds an important role in mass mobility. Sustainable usage combined with the increase in vehicle volume can lead to road damage, which eventually affects its construction condition and has implications for quality, comfort, safety, and traffic flow. Therefore, periodic analysis of road surface damage is crucial to determine whether the road is in good condition or requires repair and maintenance. Jalan Raya Ciherang in Bogor Regency is categorized as a busy district road, with a length of 2 km, serving as a secondary local road. The Surface Distress Index (SDI) and International Roughness Index (IRI) methods were used to assess the road surface condition. By comparing visual assessments and using the Roadroid application, the results were more effective in determining the level of damage and finding appropriate actions to solve the problem. The analysis showed that the average percentage of road damage using the SDI and IRI methods, the highest percentage of SDI values indicates a good condition at 50%, while the highest percentage of IRI values indicates a combination of good and fair conditions, both at 37.50%. Referring to the data on determining the type of road condition management from Bina Marga, 2011, it was necessary to perform routine maintenance. According to information from Kebina-Margaan, and Dinas Pekerjaan Umum 2007 regarding road service conditions, Jalan Raya Ciherang falls into the category of Mantap service condition.